Співвідношення політичної ідеології та політичної науки - Гайдай, Сергій Вікторович (My University, 2011)
Розглянуто активний процес формування нової політичної системи взаємодії політичної ідеології та політології, становлення якої в нашому суспільстві відбувається складно та суперечливо. На жаль, власний досвід України обмежений, і наша країна практично не має сучасного досвіду побудови системи політології. Тому найважливішими перспективами співвідношення політичної ідеології та політології є побудова демократичної, правової, соціальної, конкурентоспроможної та ефективно функціонуючої держави. The active process of forming a new political system of interaction between political ideology and political science is considered, the formation of which in our society is taking place in a difficult and contradictory manner. Unfortunately, Ukraine's own experience is limited, and our country has practically no modern experience in building a system of political science. Therefore, the most important prospects for the correlation of political ideology and political science are the construction of a democratic, legal, social, competitive, and effectively functioning state.
Keywords: політична ідеологія; political ideology; політична наука; political science